Understanding Musical Success Beyond Hit Songs: Characterization and Analyses of Musical Careers - Seufitelli, Danilo Boechat; Moro, Mirella M. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e Web, 2024)
Streaming brought the high data availability over the web associated with music consumption and listener preference. With such data, we can extract relevant knowledge, such as what can lead some songs to success and others not. In this scenario, Hit Song Science emerged, an area of study focused on revealing the dynamics of success in the music industry. Collecting hits can lead artists to experience periods of success far beyond the "ordinary" periods known as Hot Streaks. In this sense, understanding the factors of how the different profiles of artists stand out and reach their most successful periods can be crucial for the music industry, which deals with the constant natural evolution of the market and needs to reinvent itself to satisfy the desires of its consumers: connect successful music and artists. Thus, this thesis aims to identify the characteristics that lead artists to reach their most successful periods.